Modulating leaf thickness and calcium content impact on strawberry plant thermotolerance and water consumption - Xu, Xiangnan; Sun, Yanxin; Liu, Fulai (Plant growth regulation, 2022)
Late spring strawberry production is challenged by high solar radiation and temperature. This study aimed to test the efficacy of different treatments in reducing strawberry water consumption and improving its fruit quality. The pot experiment focused on rhizosphere treatment, plants were subject to three irrigation regimes: full irrigation (FI), partial rhizosphere drying (PRD), and deficit irrigation (DI); coupled with two root volumes: large (L) and small (S). The field experiment focused on transpiration control, including three different leaf sprays: kaolin (KA), sodium silicate (SI), and salicylic acid (SA); aligned with two leaf removal methods: evenly remove (JY) and traditional remove (Tr). The results showed that irrigation reduction and root confinement respectively increased leaf abscisic acid (ABA) concentration by 19.5% and 25.6%, with a minor increase in leaf calcium concentration. Irrigation reduction and root confinement reduced stomatal conductance by 22.1% and 12.3% and reduced specific leaf area (SLA) by 15.6% and 11.4%, respectively, compared to the control. In relation to the non-spray treatment, SI and KA led to the reduction of stomatal conductance and leaf calcium concentration, but only SI reduces SLA by 14.5%. Among these treatments, irrigation reduction and root confinement reduced stomatal conductance through the elevation of leaf ABA, calcium concentration, and leaf thickness, while silicate leaf spray suppressed the transpiration by thickening the leaf. In addition, the plant’s response to root confinement depended on water supply, under FI, leaf calcium concentration decreased with stomatal conductance under smaller root volume, otherwise, it increased under root confinement. It was concluded that irrigation reduction, root confinement, and silicate spray could reduce water consumption, and improve strawberry plants' thermotolerance and drought resistance as well as adaptability to the high light environment.